An Old song in a New Way: About the Progression in the Personal Income Tax - M. M. Yumaev (Финансы: теория и практика)
The issues of choosing between proportional and progressive taxation of personal income and assessment of the principle of fair taxation in relation to these methods accompany the centuries-old history of world tax policy, which is the relevance of the research, being the subject of discussions of Russian and foreign scientists. The purpose of the study is to develop the idea of taxation of income of the population in Russia, taking into account the principle of fair taxation. The theoretical objectives of the study include an analysis of the validity of the method of taxation chosen, as well as an analysis of the progressive method of taxation, which allows for a fair redistribution of income through the progression of rates and an adequate system of tax deductions. The practical objectives of the study are to study the influence of income taxation methods on the formation of budget revenues and incomes of the population, to assess the “shadow” fiscal potential of income, to determine the level of demand and significance of tax deductions. As a result of the research, it has been scientifically proven that proportional taxation and weak progression discredit the principle of vertical equity, lead to a hidden progression in the withdrawal of income, have no obvious positive effect on capital outflow and, in combination with insurance premiums, affect the size of the potential tax base. The practical significance of the study is to develop concrete proposals for the methodological development of personal income tax through differentiated tax deductions, tax mechanisms for strengthening the institution of family and marriage, and the expansion of the tax base.